Teacher’s competence and performance: A systematic theoretical study - Alifah Diantebes Aindra; Aji Prasetya Wibawa; Didik Nurhadi (International Journal of Education and Learning, 2022)
One of the goals of vocational revitalization is the improvement of educators/teachers’ competence. This is considered important as the competence is the main capital for managing learning process, besides knowing the functions and duties as a teacher in the classroom, which can be in the form of the teachers’ performance. However, these two things are not obtained instantly, but a process and several factors have influenced them as well. This study aims to find some factors that can affect competence and performance based on the previous research as well as potential factors that likely influence. By using the Systematic Literature Review (SLR) method, seven factors and three potential factors along with their measurement indicators have been proven to influence the competence and the performance. Thus, it can be concluded that to find out the relationship between potential factors such as social media, a religion and a healthy lifestyle on the teachers’ competence and performance, it is necessary to prove the findings in this article.